Prioritas Pengembangan Wisata Pantai Paseban Kecamatan Kencong Kabupaten Jember Berbasis Persepsi Masyarakat - Evi Minarsih; Rindang Alfiah; Indra Nurtjahjaningtyas (MATRAPOLIS: Jurnal Perencanaan Wilayah dan Kota, 2023)
Paseban Beach is one of the beaches designated as nature tourism in the RTRW of Jember Regency in 2015-2035. In the strategic plan (RENSTRA) of Jember Regency for 2016-2021 Paseban Beach is also designated as nature tourism. Based on the RIPPDA document of Jember Regency in 2015, Paseban beach was designated as a natural tourism area with potential activities in the form of beach tourism. In the existing condition, the allotment of Paseban beach is used as nature tourism with massive tourism development. This is due to several factors, namely the tourism component that has not been fulfilled and human resources that are not ready for the development of Paseban beach tourism. So that many impacts occur on Paseban Beach tourism. One of the most prominent impacts on Paseban beach tourism is the problem of waste caused by tourist activities that are not balanced with the availability of tourism components and public awareness. This study uses primary data in the form of field observations and questionnaires and secondary data, namely literature studies and agency surveys. The research respondents used were sourced from tourist visits to Paseban Beach in 2015 as many as 15,000 people. Then the number of respondents was determined using the slovin technique with the results of 100 respondents. The method used in this study is a descriptive method to identify the characteristics of the tourism component of Paseban Beach and Importance Performance Analysis (IPA) to determine the priority of developing the tourism component of Paseban Beach. Based on the analysis that has been done, the results obtained are development priorities in quadrant A, namely gazebos, sign boards and tourist maps.